Numerical Simulations of Stress Intensity Factors and Fatigue Life in L-Shaped Sheet Profiles - Ferdinand Dömling; Florian Paysan; Eric Breitbarth (Metals)
The assessment of fatigue cracks is an elementary part of the design process of lightweight structures subject to operational loads. Although angled sheets are standard components in forming technology, fatigue crack growth in geometries like C- and L-sections has been little-studied and is mostly limited to crack growth before the transition through the corner. In this study, fatigue crack propagation is simulated to explore the influence of sheet thickness, corner angle and corner radius on the fatigue life in an L-section. The stress intensity factor (SIF) is derived as the driving force of crack growth over the full crack path. Special attention is paid to the evolution of the SIF in the radius sub-section and its implications on the fatigue life. The results show that the SIF in an angled sheet for given loading conditions and crack lengths cannot be readily approximated by the SIF in an equivalent straightened sheet. The bending angle and radius lead to crack growth retardation or acceleration effects. These findings are important for the design and optimization of forming geometries with regard to fatigue crack growth.